An investigation on levels of the empathic tendencies of elite university tennis players in terms of different variables - Atilla Pulur; Ebru Karabulut (Türk Spor ve Egzersiz Dergisi)
The research consists of a screening model aimed at evaluating the Emphatic Tendency Levels of elite university tennis players in terms of different variables. The research sample comprises 151 athletes, 68 females and 83 males, who had voluntarily responded to the survey out of 416 athletes participating to the Universities Tennis Tournament, organized by Turkish University Sports Federation (TÜSF). The Scale of Empathic Tendency (SET), developed by Dökmen, was used as the data collection tool. The Scale had been developed with a view to measure the individual potential to develop empathy in daily life. The mean and standard deviation was computed to statistically analyze the data. The t-test and Kruskal-Wallis test for non-parametric groups were employed, and outcomes were presented in tables. The statistical significance level was selected as 0.05.                As a result, no significant correlation was found between the SET scores of athletes and the age/gender variables. Nevertheless, the girls' score was higher than the boys'. Moreover, the perceived family attitude and the educational level of mothers were found to be significantly correlated with the SET scores.